Steel damage based on acoustic emission. (May 2015) - Wang, H. W.; Yu, H. M.; Xiao, H. Q.; Han, Z. Y.; Luo, H. Y.
<x content-type="archive" xml:space="preserve">Abstract</x> This study focused on the damage analysis of Q345 steel in the tensile test with acoustic emission technique. First, Q345 steel-plate specimens in the tensile test were monitored with acoustic emission, and two typical acoustic emission signals were obtained based on the test data: (i) the lower amplitude and higher energy acoustic emission signals in yielding stage and (ii) the higher amplitude and lower energy acoustic emission signals in micro-plastic deformation and strain hardening stage. Second, the related acoustic emission behaviour and deformation properties were analysed, and the results showed that the former acoustic emission signals could be attributed to the dislocation multiplication and unpinning from Cottrell atmosphere or dislocation tangling, while the latter acoustic emission signals might be generated by the simultaneous motion of high-density dislocations during Luders band propagation.